Cross-Border Traders in Northern Laos : Mastering Smallness - Rowedder, Simon (Asian borderlands, 2022)
Northern Laos has become a prominent spot in large-scale, top-down mappings and studies of neoliberal globalisation and infrastructural development linking Thailand and China, and markets further beyond. Yet in the common narrative, in which Laos appears as a weak victim helplessly exposed to its larger neighbours, attention is seldom paid to local voices. This book fills this gap. Building on long-term multi-sited fieldwork, it accompanies northern Lao cross-border traders closely in their transnational worlds of mobilities, social relations, economic experimentation and aspiration. Cross-Border Traders in Northern Laos: Mastering Smallness demonstrates that these traders' indispensable but often invisible role in the everyday workings of the China-Laos-Thailand borderland economy relies on their rhetoric and practices of 'smallness'--of framing their transnational trade activities in a self-deprecating manner and stressing their economic inferiority. Decoding their discursive surface of insignificance, this ethnography of 'smallness' foregrounds remarkable transnational social and economic skills that are mostly invisible in Sino-Southeast Asian borderland scholarship.